What Citizens Want in Terms of Intra-Party Democracy: Popular Attitudes towards Alternative Candidate Selection Procedures. (October 2017) - Close, Caroline; Kelbel, Camille; van Haute, Emilie
Reforms of intra-party decision-making processes often rest on the idea that citizens want more direct say in these processes, but empirical data to support this claim are scarce. Using original data from the 2014 PartiRep voter survey in Belgium, this article explores the extent to which citizens support alternative intra-party processes. It shows that voters have heterogeneous preferences in terms of candidate selection procedures and that these are not random. 'Disaffected' citizens tend to support open procedures, whereas critical citizens tend to prefer closed selectorates, that is, intra-party actors. It also finds that voters' preferences for intra-party models of democracy match their preferences for models of democracy at the system level. Our findings confirm that citizens do have clear preferences for how parties should organise and that these match their general views on how democracy should work.